Cross-cultural interaction in polylingual space of the region - Tameryan, T.Y. (Vestnik Rossijskogo universiteta družby narodov. Seriâ: Teoriâ âzyka, semiotika, semantika (Online), 2017)
Proceeding from the analysis of 236 texts of anecdotes in Russian and Osetian languages collected from different sources Inteernet sites, scripts, periodicles, etc., the aricle treats stereotypical features of text characters representing various subethnic groups, reveals the interethnic interaction of bearers of different dialects of the Osetian language, describes heterostereotypes, exicting in the North Osetian linguoculture. The set of anecdote texts inder analysis is circulating in both republics North Osetia - Alania and South Osetia., and the objects of irony and fun are bearers of dogors’ and irons’ dialects, and species of those dialects - kudars’ and ksns’ ones.